KNOWLEDGE OF CORONARY ARTERY DISEASE AMONG CARDIOVASCULAR PATIENTS AT TRA VINH PROVINCIAL GENERAL HOSPITAL AND ASSOCIATED FACTORS IN 2024 - Le Hoang Giang, Ngo; Tai Hoang Hieu, Lam (Journal of Health and Aging, 2025)
To assess patients’ average level of knowledge regarding coronary artery disease and its associated factors at Tra Vinh Provincial General Hospital in the year 2024. A descriptive cross-sectional study was conducted on 128 patients diagnosed with coronary artery disease who came for examination and surgical treatment at the Cardiology Clinic at Tra Vinh Provincial General Hospital from May 2024 to July 2024 using the CADE-Q SV questionnaire. Our research results showed that 76.6% of patients had average knowledge and 23.7% of patients had poor knowledge; no patients had good knowledge; the rate of patients answering correctly for all questions was 45.04%; there was no correlation found between the knowledge of patients with coronary artery disease at Tra Vinh General Hospital and the factors surveyed at the time of the survey. Our research results showed that the knowledge of patients with coronary artery disease at Tra Vinh General Hospital in this study was still low, and there was no factors related to the rate of patients’ knowledge about coronary artery disease have been found.
Keywords: coronary artery disease; knowledge; Tra Vinh Provincial General Hospital